Covid-19 vaccine hesitancy, conspiracist beliefs, paranoid ideation and perceived ethnic discrimination in a sample of University students in Venezuela. Issue 47 (16th November 2021) - Andrade, Gabriel
Abstract: Due to complex social, political and economic causes, Venezuela has encountered difficulties managing the Covid-19 pandemic. Although a vaccination program has started, it is still comparatively slow and largely inefficient. One particular challenge has been vaccine hesitancy. Venezuelan policymakers have traditionally not rendered much attention to ethnic disparities. In this study, we assess whether vaccine hesitancy varies across ethnic groups, in a sample of 273 Venezuelan university students. Results come out showing that marginalized ethnic groups in Venezuela are more prone to vaccine hesitancy, and also have greater levels of acceptance regarding conspiracy theories. Coefficients of correlation of ethnic discrimination with vaccine hesitancy and conspiracy beliefs are moderate. Coefficients of correlation of paranoid ideation with vaccine hesitancy and conspiracy beliefs are weak. This suggests that in order to successfully complete the vaccination program, policymakers in Venezuela must begin to approach racial disparities.